2021
DOI: 10.3389/fcvm.2021.711547
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive Global and Regional Myocardial Work Predicts High-Risk Stable Coronary Artery Disease Patients With Normal Segmental Wall Motion and Left Ventricular Function

Abstract: Background: Previous studies suggested that myocardial work (MW) may identify abnormalities in the left ventricular (LV) function and establish a more sensitive index for LV dysfunction at the early stage. This study aimed to explore the value of global and regional MW parameters in predicting high-risk stable coronary artery disease (SCAD) patients with normal wall motion and preserved LV function.Patients and Methods: A total of 131 patients, who were clinically diagnosed as SCAD with normal wall motion and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 51 publications
0
11
0
1
Order By: Relevance
“…We screened 1145 articles, of which 187 full‐texts were retrieved and reviewed for possible inclusion. Subsequently, we included a total of five studies 2,7–10 enrolling 501 patients (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…We screened 1145 articles, of which 187 full‐texts were retrieved and reviewed for possible inclusion. Subsequently, we included a total of five studies 2,7–10 enrolling 501 patients (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Abnormal myocardial work appears to be highly specific to the myocardial region where hypertrophic cardiomyopathy is involved. A recent study showed regional myocardial work has great potential for non-invasively predicting high-risk patients with stable coronary heart disease and normal wall motion and preserved left ventricular function [ 17 ]. Myocardial work is derived from 2D strain, and although myocardial strain has been applied widely [ 18 ], the observer variability of segmental strain is a well-known disadvantage compared with the global strain [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…When necessary, automatic endocardial recognition was manually adjusted to ensure correct ‘anchorage’ of the algorithm to the mitral annulus, exclude papillary muscles and chordae from tracking and correctly include the LV apex. The region of interest (ROI) was eventually adjusted to ensure tracking of the whole myocardial thickness [ 19 ]. LV outflow pulsed Doppler was used to time end systole [ 20 ].…”
Section: Methodsmentioning
confidence: 99%